Iron-catalyzed amidation of 1,3-dicarbonyl compounds. - Ong, Wei Ting. (2010)
An efficient Fe-catalyzed amidation of 1,3-dicarbonyl compounds to α-amidated products through C(sp3)-H functionalization is achieved via 2 methods; indirect method of using PhI=NTs (Ts = toluene-4-sulfonyl) as nitrogen source and direct method of using PhI(OAc)2 as oxidant and TsNH2 as nitrogen source. The reaction was applied successfully to a variety of aromatic and aliphatic 1,3-dicarbonyl compounds with electron-donating, electron-withdrawing and sterically encumbered groups present in the substrates. The amidated products were obtained in excellent yields up to 99% under mild conditions at room temperature.